Eco Smart Backpack / Aliyah Syafiya Abdul Rahman ... [et al.] - Abdul Rahman, Aliyah Syafiya; Mansor, Nur Adila; Zulkifli, Siti Zuhairah Hazwani; Norizan, Nur Syuhada; Zainal Abidin, Fadhilah; Sukur, Noordiana (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The backpack is a perfect travel companion for any journey because it is designed to replace all other luggage, which is frequently used by hikers, casual travellers and backpackers. Backpack is very necessary when traveling because it can make it easier and lighter for traveller to carry their belongings. However, there are some common backpacking problems; from unexpected weather conditions and equipment failures to navigation issues and safety concerns. Therefore, a product named Eco Smart Backpack was created to solve these problems. Furthermore, by integrating the recycle concept into this product, it is not only benefitting traveller but also the environment. In the long term, this product indirectly enables us to support a circular economy and minimise waste and landfill building. The objective of Eco Smart Backpack is to create a multi-function backpack from recycle materials and household items that assist traveller during their trips. In the process, several additional parts have been added to the used backpack. Every component has a distinct purpose; the pocketed GPS tracker, a safety whistle, a one-step poncho, a hiking stick and a used backpack. The ideal consumers for this Eco Smart Backpack are travellers, outdoor enthusiasts, novice hikers, and backpackers. We hope that this innovation product also helps us to protect our environment by recycling the used materials for a new purpose.